Can Experiential Games and Improved Risk Coverage Raise Demand for Index Insurance? Evidence from Kenya. Issue 1 (12th August 2020) - Janzen, Sarah; Magnan, Nicholas; Mullally, Conner; Shin, Soye; Palmer, I. Bailey; Oduol, Judith; Hughes, Karl
Abstract : Uninsured risk impedes agricultural production, but traditional indemnity insurance is not a viable option for smallholder farmers due to market failures. Weather index insurance is often touted as an alternative risk management tool. Demand for weather index insurance, however, has been weak. One possible reason is basis risk, the mismatch between index insurance payouts and individual outcomes. We estimate the impact of two interventions on preferred coverage under a real index insurance product, as revealed through an auction: ( a ) a reduction in basis risk, and ( b ) an experiential game that teaches farmers how index insurance works, with an emphasis on basis risk. We show all farmers demonstrate strong sensitivity to basis risk. The experiential game modestly increased knowledge, and experiential game participants indicate higher levels of preferred insurance coverage. Although offering a lower basis risk insurance product and playing an experiential game both increase preferred coverage in isolation, there is no additional impact of doing both. We adapt a theoretical model of misattribution bias to demonstrate how reference‐dependent learning with loss aversion could lead to this unexpected result.